Determinants of lost theatre capacity. Issue 9 (November 2020) - Mustafa, A.M.; Day, S.; Higginson, J.; Sharp, I.
Abstract: Secondary care Trusts nationwide are continuing to fail the 18-week referral to treatment (RTT) target despite several initiatives to improve theatre efficiency (2018 NHS England review). A limitation of wasted theatre productivity is required to alleviate pressures on waiting lists. Productivity, which is a measure of treatment time as a proportion of available/allocated time, takes into consideration variations in operator performance, early (non-funded) theatre starts, and over-run, and its analysis enables the determination of theatre downtime and lost theatre capacity. We monitored productivity over a 12-week period and performed downtime analysis as reported in the NHS Improvement national audit (NHSI). Results showed a marked but predictable variation in productivity connected to turnaround and session list scheduling. Productivity and booking efficiency correlated uniformly (Pearson's r = 0.82). Theatre downtime was analysed with respect to three components defined in the NHSI national audit: late starts, early finish, and turnaround. We found that lost theatre time was predominantly due to early finishes; late starts were infrequent. Transport time correlated unfavourably with productivity (Pearson's r = -0.29, p = 0.037) and over-run (r = 0.44), and prolonged transport times were shorter when surgery was performed in a dedicated day surgery unit. Calculating the mean transport times for lists with high compared with low productivity helped us set a benchmark for patient transport times for future audit.